Girls and adolescents with a history of childhood sexual abuse - Castañeda Chang, Ana María (2003)
A descriptive study was made based on 30 teenager-girls with history of sexual abuse who received attention at the Psychological and Gynecological Service of the Child Specialized Institute of Health from January to October 2003. The 33.2% of the girls taken by their relatives and demanding for psychological support ranges between 3 to 8 years old, the 46.2% area early adolescents, that is, their ages range from 10 to 13 and the 19l9% are middle adolescents from 14 to 17 years of age.